2020
DOI: 10.1177/0885328220927317
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of sliver nanoparticles/polyvinyl alcohol/gelatin ternary nanofiber mats for wound healing application

Abstract: Purpose In this study, we aimed to determine the regenerative and antimicrobial impact of the electrospun nanofiber mats, with/without silver nanoparticles (AgNPs), on full-thickness skin wounds in rabbits. Methods Polyvinyl alcohol was combined with gelatin to provide biocompatible electrospun binary nanofiber mats. AgNPs were added to the polyvinyl alcohol/gelatin mixture to obtain ternary nanofiber-AgNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 45 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…Moreover, the antibacterial performance was also notably enhanced due to the encapsulation of Fe 3 O 4 nanoparticles. The existing studies also reported the design and development of electrospun ternary nanofiber mats with different multifunctional performances for wound dressing applications, such as ferric oxide/gelatin/glycerol nanofiber mats [ 116 ], copper oxide nanoparticle/gelatin/PCL nanofiber mats [ 117 ], cerium oxide nanoparticle/gelatin/PCL nanofiber mats [ 118 ], sliver nanoparticle/gelatin/PVA nanofiber mats [ 119 ], tellurium nanoparticle/gelatin/PCL nanofiber mats [ 120 ], and halloysite nanotube/gelatin/PCL nanofiber mats [ 121 ].…”
Section: Electrospun Gelatin-based Nanofibersmentioning
confidence: 99%
“…Moreover, the antibacterial performance was also notably enhanced due to the encapsulation of Fe 3 O 4 nanoparticles. The existing studies also reported the design and development of electrospun ternary nanofiber mats with different multifunctional performances for wound dressing applications, such as ferric oxide/gelatin/glycerol nanofiber mats [ 116 ], copper oxide nanoparticle/gelatin/PCL nanofiber mats [ 117 ], cerium oxide nanoparticle/gelatin/PCL nanofiber mats [ 118 ], sliver nanoparticle/gelatin/PVA nanofiber mats [ 119 ], tellurium nanoparticle/gelatin/PCL nanofiber mats [ 120 ], and halloysite nanotube/gelatin/PCL nanofiber mats [ 121 ].…”
Section: Electrospun Gelatin-based Nanofibersmentioning
confidence: 99%
“…The SEM images of the hybrid nanofiber mats showed a combination of smooth, beads-free, and uniform fibrous morphologies. The in vivo studies showed an accelerated wound healing process when the full-thickness skin wounds in rabbits were treated with both hybrid nanofiber mats incorporated with nanoparticles and pristine hybrid nanofiber mats [ 111 ]. Cai et al, prepared nanofibrous membranes that are based on gelatin and PCL.…”
Section: Gelatin-based Hybrid Wound Dressingsmentioning
confidence: 99%
“…The targeting of chronic wound biofilms of S. aureus and E. coli was successful by using nano silver-loaded polyvinyl alcohol-based fibres [ 162 ] with high mechanical stability. Both nanofiber/nanofiber-AgNPs mats are found to combat microbial invasion into the wound bed [ 163 ].…”
Section: Nanoplatforms Against Wound Biofilmsmentioning
confidence: 99%